1989
DOI: 10.1021/jo00283a024
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis by cucurbituril. The significance of bound-substrate destabilization for induced triazole formation

Abstract: Chemical Research (RIKEN) for donation of rutheniumcatalysts. We are also indebted to Professor S. Suzuki of our department for the suggestion for the malonaldehyde assay. We also thank Professor K. Hirao of our University for his helpful guidance in conducting MO calculations.A mechanistic investigation is described for the cycloaddition induced between RNH2+CH2C=CH and RNHz+CH2CHzN3 (R = H, t-Bu) consequent to encapsulation by the polycyclic molecular receptor cucurbituril (C3BH9sNU012). The reaction is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
366
1
7

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(387 citation statements)
references
References 4 publications
(6 reference statements)
9
366
1
7
Order By: Relevance
“…44,45,87,88 Since 1,2,3-triazoles are basic aromatic heterocyclic compounds, they are bioisosteres of aromatic rings and double bonds. 65,66 Additionally, the aforementioned physicochemical properties of 1,2,3-triazole moiety together with similarity to amide bond, make it a useful linker to generate "twin drugs", 42,67,83 bidentate inhibitors, [83][84][85]89 linkers to immobilized fluorescent tags or small molecules, 71 and anion receptors. …”
Section: The Huisgen's 13-dipolar Cycloadditionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45,87,88 Since 1,2,3-triazoles are basic aromatic heterocyclic compounds, they are bioisosteres of aromatic rings and double bonds. 65,66 Additionally, the aforementioned physicochemical properties of 1,2,3-triazole moiety together with similarity to amide bond, make it a useful linker to generate "twin drugs", 42,67,83 bidentate inhibitors, [83][84][85]89 linkers to immobilized fluorescent tags or small molecules, 71 and anion receptors. …”
Section: The Huisgen's 13-dipolar Cycloadditionmentioning
confidence: 99%
“…In situ click chemistry screening of binary mixtures of tacrine/phenylphenanthridinium-based building blocks for the discovery of bivalent inhibitors to AChE. 91,98 curbituril, a macrocycle made of glycouril, 89 Lewis et al were the first to investigate the potential of Huisgen's cycloaddition for application to target-guided synthesis. 91 In their proof-of-concept study, they selected enzyme acetylcholinesterase (AChE; EC 3.1.1.7) which plays a vital role in neuro-transmission in central and peripheral nervous system.…”
Section: In Situ Click Chemistry Using Acetylcholinesterase As a Tmentioning
confidence: 99%
“…Previous work that inspired Sharpless included that by Mock and colleagues, who elegantly demonstrated that cucurbituril, a nonadecacyclic cage, acted as an entropic trap for the azide and alkyne and kinetically enhanced the rate of the cycloaddition by 10 5 -fold. [105] In addition, work by Bertozzi demonstrated the power of bioorthogonal reactions to probe biological systems. [106,107] The first biological target explored by Sharpless and colleagues in their investigation of RAS was acetylcholine esterase (AChE), which has two distinct binding pockets in close proximity to one another.…”
Section: Figure 21mentioning
confidence: 99%
“…Cucurbiturils have been shown to have a variety of potential applications. The ability of CB[n] to act as a catalyst for a chemical reaction was recognized by Mock relatively soon after his characterization of CB [6] [38,39]. He realized that, since CB [6] has two electron rich portals, it had the potential to bring two cationic reactants in close proximity, as well as in specific orientations, so that the two reactants could undergo an accelerated reaction if they were simultaneously bound with the macrocycle.…”
Section: Hostmentioning
confidence: 99%